The process of handcuffing persons - Dalcaran, Cristina-Andreea (Eximia, 2023)
In Romania, the police are among the institutions whose aim is to defend civil rights and liberties, as well as train citizens to comply with the laws or punish those who deviate from the rules and principles of a modern and fair society. The police generally perform work in the field, having direct contact with citizens, to ensure public order and peace, tracking and enforcement of the law. The policeman is obliged to intervene on any person, regardless of the position that person holds in society, gender or race, when he endangers the security of the state, the rights and freedoms of other people. In some situations, the warning given by the police to a person is enough for that person to stop committing illegal acts, but there are also situations in which it is necessary to use the means of immobilization, force or even the weapons provided. These situations endanger the physical integrity of the policeman or even his life, because of violent people. The utility of the existence of theories and practices of police intervention is caused by the fact that there are no complete articles in the law regarding the rights and freedoms of police officers on duty, for solving all cases. Compliance with these theoretical and practical rules protects police officers from abuses and deviations in interventions. Missions will be solved successfully and carried out, only if the most effective procedures and methods are respected, which is exactly why the policeman is obliged to respect these rules.